Assessing Plasma Levels of α-Synuclein and Neurofilament Light Chain by Different Blood Preparation Methods - Chang, Kuo-Hsuan; Liu, Kou-Chen; Lai, Chao-Sung; Yang, Shieh-Yueh; Chen, Chiung-Mei (Frontiers in Aging Neuroscience, 2021)
α-Synuclein and neurofilament light chain (NFL) are potential biomarkers for Parkinson’s disease (PD). However, inconsistent preanalytical preparation of plasma could lead to variations in these biomarkers. Different potassium salts of ethylenediaminetetraacetic acid (EDTA) and different centrifugation temperatures during plasma preparation could affect the results of α-synuclein and NFL measurements. Here we prepared plasma from 8 patients with PD and 7 healthy controls (HCs) by using di- and tri-potassium (K2- and K3-) EDTA tubes, and recruited a separated cohort with 42 PD patients and 40 HCs for preparations of plasma by centrifugation at room temperature and 4oC, respectively, in K2-EDTA tubes. The plasma levels of α-synuclein and NFL in K2- and K3-EDTA were similar. However, the levels of α-synuclein in the plasma prepared at 4oC (101.57 ± 43.43 fg/mL) were significantly lower compared with those at room temperature (181.23 ± 196.31 fg/mL, P<0.001). Room temperature preparation demonstrated elevated plasma levels of α-synuclein in PD patients (256.60 ± 50.20 fg/mL) compared with the HCs (102.10 ± 0.66 fg/mL, P<0.001), whereas this increase in PD was not present by preparation at 4oC. Both plasma preparations at room temperature and 4oC demonstrated consistent results of NFL, which are increased in PD patients compared to HCs. Our findings confirm that K2- and K3-EDTA tubes are interchangeable for analyzing plasma levels of α-synuclein and NFL. Centrifugation at 4oC during plasma preparation generates considerable reduction and variation of α-synuclein level that may hinder the detection of α-synuclein level changes in PD.